Microstructural, mechanical, corrosion and cytotoxicity characterization of the hot forged FeMn30(wt.%) alloy - Čapek, Jaroslav; Kubásek, Jiří; Vojtěch, Dalibor; Jablonská, Eva; Lipov, Jan; Ruml, Tomáš (Materials science & engineering. C, Materials for biological applications, 2016)
An interest in biodegradable metallic materials has been increasing in the last two decades. Besides magnesium based materials, iron-manganese alloys have been considered as possible candidates for fabrication of biodegradable stents and orthopedic implants. In this study, we prepared a hot forged FeMn30 (wt.%) alloy and investigated its microstructural, mechanical and corrosion characteristics as well as cytotoxicity towards mouse L 929 fibroblasts. The obtained results were compared with those of iron. The FeMn30 alloy was composed of antiferromagnetic γ-austenite and ε-martensite phases and possessed better mechanical properties than iron and even that of 316 L steel. The potentiodynamic measurements in simulated body fluids showed that alloying with manganese lowered the free corrosion potential and enhanced the corrosion rate, compared to iron. On the other hand, the corrosion rate of FeMn30 obtained by a semi-static immersion test was significantly lower than that of iron, most likely due to a higher degree of alkalization in sample surrounding. The presence of manganese in the alloy slightly enhanced toxicity towards the L 929 cells; however, the toxicity did not exceed the allowed limit and FeMn30 alloy fulfilled the requirements of the ISO 10993-5 standard.
Keywords: pevnost v tlaku; Compressive Strength; železo; Manganese; viabilita buněk; Tensile Strength; Biocompatible Materials; zvířata; Animals; myši; pevnost v tahu; Cell Line; Iron; difrakce rentgenového záření; mangan; Mice; Corrosion; buněčné linie; biokompatibilní materiály; Cell Survival; koroze; X-Ray Diffraction